An ordered integrated electrode with ultra-low Pt loading and preparation method thereof

By covering the Pt film with ultra-low Pt load on the surface of the composite ordered nanowire array carrier and forming a layered metal substrate therebetween, the problems of disordered traditional electrode structures and low Pt utilization are solved, and an efficient and stable fuel cell electrode is achieved.

CN115799543BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211494103.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-04-11
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

Traditional fuel cell electrodes have problems such as disordered structure, low Pt utilization rate and poor stability. Especially in high potential and strong acidic environments, the nanoparticles of the catalyst are prone to loss and agglomeration, affecting the electrode activity.

Method used

Using an ordered integrated electrode with ultra-low Pt load, a Pt film of nano or sub-nano-scale thickness is formed between the Pt film and the carrier, such as Pd or Pd-M.

Benefits of technology

It realizes orderly structure, integrated electrodes, reduces costs, improves the utilization rate of precious metals, and improves the chemical stability and reaction efficiency of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799543B_ABST
    Figure CN115799543B_ABST
Patent Text Reader

Abstract

The present invention discloses an ultra-low Pt loading integrated electrode and a preparation method thereof. Based on an ordered array of composite nanowires, the structure is ordered and the electron and proton conduction functions are coupled simultaneously. Based on an ordered composite carrier, binary or ternary active components of Pt and transition metals are prepared on the carrier surface by adsorption reduction and underpotential deposition plus substitution reaction, respectively, to form an ordered integrated electrode with high catalytic activity. The electrode structure of the present invention is ordered, which is conducive to the efficient transmission of electrode reaction substances. At the same time, the proton and electron conduction functions are coupled, which can effectively improve the electrode reaction efficiency. The active components such as noble metal Pt can form an ultra-thin film with an atomic layer thickness to coat the surface of the nanowire array, significantly reducing the amount of noble metals used, while avoiding the problems of agglomeration and dissolution of traditional nanoparticle catalysts that affect stability during use. The ordered integrated electrode has great application prospects in fuel cells and water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to an ordered integrated electrode with ultra-low Pt loading and a preparation method thereof, and relates to the application fields of nanomaterials, electrochemical synthesis, fuel cells and water electrolysis cells. Background technology:

[0002] Membrane electrodes are the core components of fuel cells or water electrolyzers (the reverse process of fuel cell reactions). Their materials and structures directly affect the performance, life and cost of the battery. Traditional fuel cell electrodes have the characteristics of disordered structure, low Pt utilization and poor stability. This is because in the preparation process of traditional structure electrodes, the catalyst and proton conductor are directly mixed to form a slurry. The catalyst and proton conductor are disorderly distributed in the prepared catalytic layer, which is not conducive to the construction of an efficient three-phase reaction interface. In addition, the disordered structure cannot form continuous through-holes, which is not conducive to the transmission of reaction gases and the discharge of water. Ordered electrode structures provide new ideas for the research of membrane electrodes. Ordered electrodes usually have relatively ordered gas-liquid / electron / proton transmission channels, which can reduce the gas-liquid mass transfer resistance, increase the effective active area and Pt utilization to a certain extent, and thus improve battery performance. Therefore, it has become a trend in the research and development of membrane electrodes.

[0003] The main direction of ordered electrode research is usually achieved by preparing structurally ordered electrode carriers. The materials generally used as ordered electrode carriers include carbon nanotubes / wire arrays, metal oxides / nitrides, conductive polymers / polymer materials, etc., and then Pt or Pt / C nanoparticle catalyst active components are loaded / attached on the surface of the ordered carrier to prepare a catalytic electrode.

[0004] Patent CN103887531A discloses an ordered gas diffusion electrode and its preparation method. The catalytic electrode is composed of conductive polymer nanowires arranged in an orderly manner on the surface of the gas diffusion layer and diethylene glycol diacrylate (PDDA) doped on the surface interacting with Pt catalyst nanoparticles. The invented ordered membrane electrode has the advantages of high Pt utilization and high stability, which can effectively reduce the cost of fuel cell catalysts; at the same time, it can effectively enhance the mass transfer of fuel in the catalytic layer, thereby improving fuel utilization. However, in this type of ordered electrode, the catalytically active component is still Pt nanoparticles. In the high-potential and strongly acidic environment of the fuel cell, there are inevitable problems such as the loss and agglomeration of nanoparticles, which affect the activity of the electrode.

[0005] Patent CN106410228A discloses an ordered catalyst layer and preparation method for a proton exchange membrane fuel cell. Fe, Co, Ni or their alloys are loaded on the surface of stainless steel, and then a carbon layer is prepared by CVD. An ordered PPy array is polymerized on the surface by an electrochemical polymerization method, and one or two metal particle catalysts are first loaded on the array, and then the PPy array coated with the catalyst is transferred to a Nafion membrane to construct an ordered thin-layer catalyst layer electrode. The catalyst layer prepared by this method does not contain a proton conductor, and the electrode reaction efficiency will be subject to certain limitations. The preparation process of the electrode requires a transfer operation, which will affect the preparation efficiency of the electrode and the integrity of the electrode structure. In addition, the active components of the electrode also exist in the form of metal nanoparticles. Summary of the invention:

[0006] The purpose of the present invention is to provide an ordered integrated electrode with ultra-low Pt loading and a preparation method thereof, which has the advantages of orderly structure, electrode integration, reduced cost, and improved utilization of precious metals.

[0007] The above technical objectives of the present invention are achieved through the following technical solutions: an ordered integrated electrode with ultra-low platinum loading, comprising a catalytic layer and a gas diffusion layer, characterized in that: the catalytic layer comprises a carrier, an active component and a metal substrate; the active component is Pt; the metal substrate is Pd or Pd-M, and the carrier is a composite ordered nanowire array; the active component Pt is coated on the surface of the composite ordered nanowire array carrier in the form of a thin film with a nanometer or subnanometer thickness; the metal substrate is located in a layered form between the Pt thin film and the composite ordered nanowire array carrier; M in the Pd-M is a precious metal.

[0008] Furthermore, in the above technical solution, the thickness of the film is 0.1nm to 3nm.

[0009] Furthermore, in the above technical solution, the Pd or Pd-M loading on the electrode surface is 50-100 μg / cm 2 .

[0010] Furthermore, in the above technical solution, the composite ordered nanowire carrier is a composite of a conductive polymer and a proton conductor, the length of the composite ordered nanowire array is 2-15 μm, the diameter is 50-200 nm, and the loading amount of the noble metal Pt on the electrode surface is 2-50 μg / cm 2 .

[0011] The present invention provides a method for preparing the above-mentioned electrode, which specifically comprises the following preparation steps:

[0012] 1) Preparation of composite ordered nanowire array carrier

[0013] In an electrolyte containing a proton conductor and a conductive polymer monomer, a composite nanowire ordered array carrier is prepared by self-catalytic growth on a gas diffusion layer using a cyclic voltammetry scanning method combined with a constant potential method or a cyclic voltammetry scanning method combined with a constant current method; the gas diffusion layer is carbon paper or carbon cloth

[0014] 2) Preparation of metal substrate layer

[0015] The composite ordered nanowire array carrier of step 1) is used as the processing object, and a metal base layer of Pd or Pd-M is prepared by a continuous ion layer adsorption reaction method; wherein M in the Pd-M is a noble metal;

[0016] 3) Preparation of Pt thin films with ultra-low Pt loading

[0017] In the three-electrode system, the metal substrate layer in step 2) is used as the working electrode and is placed on a Cu 2+ In the electrolyte solution 2, an inert gas (Ar and / or N2) is introduced into the solution to saturate it, and the unit sublayer Cu is deposited on the surface of the metal substrate layer by using the underpotential deposition technology. Then, under the protection of the inert atmosphere (Ar and / or N2), the working electrode is transferred to the Pt-containing 2+ In the precursor solution, a Pt single atomic layer based on a composite ordered carrier is prepared by substitution reaction, that is, an ordered integrated electrode is obtained;

[0018] Alternatively, the underpotential deposition of Cu and the replacement reaction of Pt are repeatedly performed to prepare a continuous Pt thin film catalytic electrode with different atomic layer thicknesses, for example, the underpotential deposition of Cu and the replacement reaction of Pt are repeatedly performed 1-5 times.

[0019] Furthermore, in the above technical solution, the preparation method of the composite ordered nanowire array carrier in step 1) is specifically as follows:

[0020] a. preparing an electrolyte solution 1, wherein the electrolyte solution 1 comprises a conductive polymer monomer, a proton conductor, a structure directing agent and a phosphate buffer;

[0021] b. Using a carbon carrier as a reaction substrate, placing the electrolyte solution of step a in a constant temperature environment, and preparing a composite nanowire ordered array carrier of polypyrrole doped with perfluorosulfonic acid resin on the carbon carrier by self-catalytic growth using a cyclic voltammetry scanning method combined with a constant potential method, or a cyclic voltammetry scanning method combined with a constant current method;

[0022] The proton conductor is a perfluorosulfonic acid resin, the conductive polymer is polypyrrole, and the monomer of the conductive polymer is a pyrrole monomer.

[0023] Further, in the above technical solution, in step 1)a, the concentration of the pyrrole monomer is 0.5-1M; the structure directing agent is one of a mixed solution of sodium hexadecyl sulfonate, sodium hexadecylbenzene sulfonate and sodium p-toluene sulfonate; the concentration of the structure directing agent in the electrolyte solution 1 is 0.5-1M; the mass fraction of the perfluorosulfonic acid resin in the electrolyte solution 1 is 0.1%-10%;

[0024] In step 1) b, the carbon carrier includes carbon paper, carbon cloth, or other carbon fibers other than carbon paper and carbon cloth;

[0025] The specific steps of the cyclic voltammetry scanning method are as follows: firstly, the carbon support is activated by cyclic voltammetry scanning, the potential range of the activation treatment is -0.241V to 0.3V, the scanning number of circles is 10-30 circles, after the activation treatment, the setting of the constant potential method is: the reaction potential is set to 0.8V-0.95V, and the reaction time is 30min-2h;

[0026] The constant temperature environment is a constant temperature water bath, and the temperature of the constant temperature water bath is 25-40°C.

[0027] Furthermore, in the above technical solution, the specific steps of preparing the metal substrate layer of Pd or Pd-M by continuous ion layer adsorption reaction method in step 2) are:

[0028] c. First, use deionized water to clean the surface of the composite ordered nanowire array carrier, and rinse repeatedly for 3-5 times;

[0029] d. Soak the composite ordered nanowire array carrier obtained in step c in a mixed solution of SnCl2 and HCl solution to make Sn 2+ Adsorbed on the surface of the composite ordered nanowire array carrier, wherein the concentrations of SnCl2 and HCl solutions are 0.5-10 mM and 0.1-1 M, respectively, the immersion time is 30 min-2 h, and the temperature of the solution is maintained at 25-35 ° C;

[0030] e. Transfer the carrier after the above immersion and immerse it in a precursor solution containing Pd, or a mixed precursor solution of Pd and a precious metal M. The immersion time is 30 minutes to 2 hours. The temperature of the solution is maintained at 25-35°C. After the reaction, a Pd or Pd-M metal base layer is obtained.

[0031] Further, in the above technical solution, in step e, the Pd precursor solution is a mixed solution of 0.5-10mM PdCl2+0.1-1M HCl or 0.5-10mM (PdCl2+MCl x )+0.1-1M HCl, wherein x is a number determined by the number of chlorine in the M metal chloride; MCl xM is a precious metal.

[0032] Further, in the above technical solution, in step 3), the end potential of the under-potential deposition of Cu on the metal substrate layer is 0-0.1V; in step 3), the Cu 2+ The second electrolyte solution is a mixed solution of 0.01-0.2 mol / L H2SO4 and 0.01-0.2 mol / L CuSO4;

[0033] The Pt-containing 2+ The precursor solution is 0.1-10 mM K2PtCl4 or 0.1-10 mM K2PtCl4.

[0034] The Pd-M metal base layer or MCl x In the above, M is one, two or more of Ru, Au and Rh.

[0035] In summary, the present invention has the following beneficial effects:

[0036] 1. The ultra-low platinum loading of the present invention is reflected in that the main precious metal active component Pt in the catalytic electrode is coated on the electrode surface in the form of an ultra-thin film (atomic layer) with a thickness of nanometer or sub-nanometer level, rather than in the form of nanoparticles. Since the nanoparticle catalyst has problems such as agglomeration and dissolution that affect stability during use, and the size of the atomic layer is much smaller than that of the nanoparticle, the present invention can achieve ultra-low Pt dosage, reduce costs, improve the utilization rate of precious metals, and has better chemical stability;

[0037] 2. The carrier of the electrode of the present invention is a composite carrier with an ordered structure, which is a composite of a conductive polymer and Nafion. The composite nanowires prepared by an electrochemical polymerization method can be controlled to couple the conductive polymer and the proton conductor (for example, perfluorosulfonic acid resin) to achieve structural ordering and coupled electron and proton conduction functions. The material transmission and the conduction of electrons and protons in the electrode reaction process are all ordered, thereby improving the reaction efficiency of the electrode;

[0038] 3. Integration is reflected in two aspects. First, the diffusion layer and the catalytic layer of the electrode are integrated. The ordered array of composite nanowires is directly grown on the gas diffusion layer such as carbon paper or carbon cloth, and then the active components are coated on the surface of the nanowires. The metal active components such as Pt of the catalytic electrode are coated on the surface of the nanowires instead of ordinary nanoparticles dispersed and attached. Second, the integration of active components is further realized in the catalytic layer, which is conducive to improving the strength and stability of the electrode structure and realizing the efficient catalytic function of the electrode.

[0039] 4. Compared with the conventional electrode, the electrode prepared by the method of the present invention has an ordered array of composite nanowires grown directly on a gas diffusion layer such as carbon paper or carbon cloth. Compared with the existing ordered structure electrode, the ordered structure carrier is prepared on stainless steel or other substrates and then transferred to the surface of the proton membrane. A large pressure is required during the transfer process, and the ordered structure is easily destroyed. The preparation method of the present invention completely avoids the above problems, and the structural order is improved, which is conducive to the efficient transmission of electrode reaction substances.

[0040] 5. The preparation of the catalyst on the surface of the ordered structure electrode carrier in the present invention adopts the underpotential deposition technology. Different from the ordinary electrodeposition or pulse electrodeposition, the present invention can accurately control the realization of Cu single atomic layer on the substrate surface by controlling the ending potential, and then realize the preparation of Pt single atomic layer to achieve the highest utilization rate of Pt; the preparation of different atomic layer thicknesses can also be achieved by controlling the number of steps to meet the diversified actual production needs. Description of the drawings:

[0041] Figure 1 It is the underpotential deposition curve of Cu on the surface of ordered composite nanowire array support;

[0042] Figure 2 This is a scanning electron microscope photo of the surface morphology of the ordered integrated electrode with ultra-low Pt loading;

[0043] Figure 3 This is a contact angle view of the integrated electrode surface after the composite nanowire array support and the preparation of the Pt film;

[0044] Figure 4 is a battery performance curve diagram using sample 1 as the cathode;

[0045] Figure 5 is a battery performance curve diagram using sample 3 as the cathode;

[0046] Figure 6 is a battery performance curve diagram using sample 4 as the cathode;

[0047] Figure 7 is a battery performance curve diagram using sample 5 as the cathode;

[0048] Figure 8 This is a battery performance curve diagram using sample 6 as the cathode. Specific implementation method:

[0049] Example 1: Preparation of ultra-low Pt loading ordered integrated electrode based on composite nanowire array and its application in fuel cell cathode

[0050] (1) Preparation of ordered nanowire array composite carrier

[0051] Using carbon paper as the substrate, a composite carrier was prepared by cyclic voltammetry in a phosphate buffer solution containing pyrrole monomer, perfluorosulfonic acid resin and a structure-directing agent. The concentration of the pyrrole monomer was 0.5 M, and the structure-directing agent was a 0.8 M mixed solution of sodium hexadecyl sulfonate and sodium p-toluenesulfonate. In the mixed solution, the molar ratio of sodium hexadecyl sulfonate to sodium p-toluenesulfonate was 1:1, and the mass fraction of perfluorosulfonic acid resin was 1%. Under a three-electrode system, cyclic voltammetry was performed in the range of -0.241 V to 0.3 V for 20 cycles, the reaction potential was 0.85 V, the reaction time was 30 min, and the electrolyte was kept in a constant temperature water bath at 35°C to obtain a composite nanowire ordered array carrier.

[0052] (2) Preparation of underpotential deposited metal substrate

[0053] The composite nanowire ordered array carrier was washed three times with a large amount of deionized water, and then immersed in a mixed solution of 5mM SnCl2 and 0.5M HCl solution for 45min at a solution temperature of 30℃; then it was transferred to a mixed solution of 2mM PdCl2 and 0.5M HCl for 1h at a solution temperature of 30℃. 2+ With Pd 2+ The redox reaction occurred and a Pd substrate layer was prepared on the surface of the ordered array carrier. The Pd loading was 50 μg / cm 2 .

[0054] (3) Preparation of Pt thin film active components on the surface of ordered array carriers

[0055] Pt thin film was prepared on the surface of Pd substrate by underpotential deposition combined with replacement reaction method: in a three-electrode system, the carrier for preparing Pd substrate as described above was used as working electrode, and in a mixed solution of 0.05M H2SO4 and 0.05M CuSO4 saturated with argon, the open circuit potential was slowly scanned to the deposition end potential of 0.01V (vs. SCE) at a scanning speed of 0.2mV / s, and underpotential deposition of Cu occurred on the Pd surface to achieve the deposition of Cu single atomic layer. The current-voltage curve of the underpotential deposition process is shown in FIG. Figure 1 As shown; under the protection of an inert atmosphere, the working electrode was transferred to a 2 mM K2PtCl4 solution, the system reaction temperature was 30°C, the reaction time was 20 min, and a replacement reaction occurred to prepare a Pt single atomic layer based on a composite ordered array carrier; an ordered integrated electrode was obtained by repeatedly performing underpotential deposition and replacement reaction of Cu; the ordered integrated electrode obtained by performing underpotential deposition and replacement reaction of Cu twice using the above method was recorded as sample 1, and the ordered integrated electrode obtained by performing underpotential deposition and replacement reaction of Cu three times using the above method was recorded as sample 2, to obtain continuous Pt thin film integrated catalytic electrodes with different atomic layer thicknesses.

[0056] Under the conditions of this embodiment, the end potential of underpotential deposition of Cu on the Pd substrate is 0.01 V. If the potential continues to decrease, the reduction current will increase sharply, and bulk reduction deposition of Cu will occur at this time. This process is uncontrollable. Therefore, the end potential is controlled at 0.01 V to control only underpotential deposition of Cu on the Pd surface to form a Cu monoatomic layer.

[0057] The surface morphology of the prepared sample 1 was observed by scanning electron microscopy. Figure 2 As shown in Figure 1, the ordered integrated electrode presents a regular nanowire array morphology, with a nanowire diameter of about 100 nanometers and a length of about 2 μm. The contact angle test was conducted on the electrode surface of sample 1 and the surface of the ordered nanowire array composite carrier. The results are shown in Figure 1. Figure 3 As shown, the left picture is the nanowire array composite carrier, and the right picture is sample 1. The nanowire array composite carrier is a high molecular material based on a conductive polymer, and its surface contact angle reaches 140.2°. After preparing the metal substrate layer and the Pt film active component, the contact angle of the electrode surface is reduced to 102.3°, and the hydrophilic properties of the electrode surface are optimized.

[0058] Sample 1 was used as cathode (Pt loading was 4.3 μg / cm 2 ), with proton exchange membrane (Nafion 211) and anode (conventional electrode, Pt loading of 50 μg / cm 2 ) assembled membrane electrode to evaluate battery performance, the electrode test results are as follows Figure 4 As shown, the open circuit voltage of a single cell is 0.95V, the cell voltage is 0.56V at a current density of 1000, and the maximum power density reaches 570mW / cm 2 To further compare with the traditional structure electrode, sample 2 was used as the cathode (Pt loading was 8.9 μg / cm 2 ) with proton exchange membrane (Nafion211) and anode (conventional electrode, Pt loading of 50 μg / cm 2 ) assembled membrane electrode for battery performance evaluation, and the battery performance of the traditional structure electrode was evaluated under the same conditions (the anode Pt loading was 50μg / cm 2 , the cathode Pt loading is 100 μg / cm 2 ), and its performance data are shown in Table 1. The maximum power density of the ultra-low Pt loading ordered integrated electrode and the traditional structure electrode reached 780mW / cm 2 and 860mW / cm 2 According to the minimum Pt usage of the electrode converted based on the cathode Pt loading, the traditional structure electrode is 0.12g / kW, while the Pt usage of the ordered integrated electrode with ultra-low Pt loading is only 0.01g / kW, which is an order of magnitude lower than that of the traditional structure electrode.

[0059] Table 1 Comparison of battery performance using sample 2 and traditional electrode as cathode

[0060]

[0061] Example 2

[0062] Preparation of ordered integrated electrodes with ultra-low Pt loading based on composite nanowire arrays and their application in fuel cell cathodes

[0063] The composite carrier was prepared by cyclic voltammetry using carbon paper as the substrate. The concentration of pyrrole monomer in the electrolyte solution was 1.0M, the structure directing agent was 1.0M sodium hexadecylbenzenesulfonate solution, and the mass fraction of perfluorosulfonic acid resin was 1%. Under the three-electrode system, the cyclic voltammetry scan was performed from -0.241V to 0.3V for 20 cycles, the reaction potential was 0.95V, the reaction time was 30min, and the electrolyte was kept in a constant temperature water bath at 35℃ to obtain a composite nanowire ordered array carrier. After the carrier was washed with deionized water three times, it was immersed in a mixed solution of 5mM SnCl2 and 0.5M HCl solution for 45min, and the solution temperature was 30℃; then it was transferred to a mixed solution of 5mM PdCl2+AuCl3 and 0.5M HCl, and the immersion time was 1h. The temperature of the solution was maintained at 30℃, and a PdAu substrate layer was prepared on the surface of the ordered array carrier, and the PdAu loading of the substrate layer was 0.1mg / cm 2 . The PdAu substrate layer prepared as above was used as the working electrode. In a mixed solution of 0.05M H2SO4 and 0.05M CuSO4 saturated with argon, the open circuit potential was slowly scanned at a scanning speed of 0.2mV / s to the deposition end potential of 0.015V (vs.SCE), and Cu was deposited on the PdAu surface by underpotential deposition. Under the protection of an inert atmosphere, the working electrode was transferred to a 2mM K2PtCl4 solution. The system reaction temperature was 30°C and the reaction time was 20min. A Pt single atomic layer based on a composite carrier was prepared. The ordered integrated electrode obtained by repeatedly performing underpotential deposition and replacement reaction of Cu was recorded as sample 3. Sample 3 was used as the cathode and was connected to a proton exchange membrane (Nafion 211) and an anode (conventional electrode with a Pt loading of 50μg / cm 2 ) assembled membrane electrode to evaluate battery performance, the electrode test results are as follows Figure 5 As shown, the open circuit voltage of a single cell is 0.96V, the battery voltage is 0.58V at a current density of 1000, and the maximum power density reaches 580mW / cm 2 After 10,000 cycles of accelerated scanning, the power density loss of the battery was only 3%, reflecting the ultra-high stability of the ordered electrode.

[0064] Example 3

[0065] Preparation of ordered integrated electrodes with ultra-low Pt loading based on composite nanowire arrays and their application in fuel cell cathodes

[0066] The composite carrier was prepared using carbon paper as the substrate by cyclic voltammetry. The concentration of pyrrole monomer in electrolyte solution 1 was 0.5 M, and the structure directing agent was a mixed solution of 1.0 M sodium hexadecylbenzenesulfonate solution and sodium p-toluenesulfonate. In the mixed solution, the molar ratio of sodium hexadecylsulfonate to sodium p-toluenesulfonate was 1:1, and the mass fraction of perfluorosulfonic acid resin was 1%. Under a three-electrode system, cyclic voltammetry was scanned for 20 cycles in the range of -0.241 V to 0.3 V, the reaction potential was 0.8 V, the reaction time was 30 min, and the electrolyte was kept in a constant temperature water bath at 35°C to obtain a composite nanowire ordered array carrier. The carrier was washed with deionized water for three times and then immersed in a mixed solution of 5 mM SnCl2 and 0.5 M HCl for 45 min at a temperature of 30 °C. It was then transferred to a mixed solution of 5 mM PdCl2 and 0.5 M HCl for 1 h at a temperature of 30 °C to prepare a Pd substrate layer on the surface of the ordered array carrier with a Pd loading of 0.1 mg / cm 2 . The Pd substrate layer prepared above was used as the working electrode. In a mixed solution of 0.05M H2SO4 and 0.05M CuSO4 saturated with argon, the open circuit potential was slowly scanned at a scanning rate of 0.2mV / s to the deposition end potential of 0.01V (vs.SCE), and Cu was deposited on the Pd surface at an underpotential. Under the protection of an inert atmosphere, the working electrode was transferred to a 2mM Na2PtCl4 solution. The system reaction temperature was 30°C and the reaction time was 20min. A Pt single atomic layer based on a composite carrier was prepared, which was recorded as sample 4. Sample 4 was used as the cathode, and was connected to a proton exchange membrane (Nafion 211) and an anode (conventional electrode with a Pt loading of 50μg / cm 2 ) assembled membrane electrode to evaluate battery performance, the electrode test results are as follows Figure 6 As shown, the open circuit voltage of a single cell is 0.93V, the cell voltage is 0.55V at a current density of 1000, and the maximum power density reaches 550mW / cm 2 .

[0067] Comparative Example 1

[0068] Preparation of ordered integrated electrodes with ultra-low Pt loading based on composite nanowire arrays and their application in fuel cell cathodes

[0069] The composite carrier was prepared by cyclic voltammetry using carbon paper as substrate. The concentration of pyrrole monomer in electrolyte solution 1 was 0.5M, and the structure directing agent was a mixed solution of 1.0M sodium hexadecylbenzenesulfonate solution and sodium p-toluenesulfonate. In the mixed solution, the molar ratio of sodium hexadecylsulfonate to sodium p-toluenesulfonate was 1:1. No perfluorosulfonic acid resin was added to electrolyte solution 1. Under the three-electrode system, cyclic voltammetry was scanned for 20 cycles from -0.241V to 0.3V, the reaction potential was 0.8V, the reaction time was 30min, and the electrolyte was kept at a constant temperature of 35℃ to obtain a composite nanowire ordered array carrier. After the carrier was washed with deionized water for 3 times, it was immersed in a mixed solution of 5mMSnCl2 and 0.5M HCl solution for 45min, and the solution temperature was 30℃; then it was transferred to a mixed solution of 5mM PdCl2 and 0.5M HCl, immersed for 1h, and the solution temperature was kept at 30℃ to prepare a Pd base layer on the surface of the ordered array carrier. The Pd substrate layer prepared above was used as the working electrode. In a mixed solution of 0.05M H2SO4 and 0.05M CuSO4 saturated with argon, the open circuit potential was slowly scanned at a scanning speed of 0.2mV / s to the deposition end potential of 0.01V (vs.SCE), and Cu was deposited on the Pd surface at an underpotential. Under the protection of an inert atmosphere, the working electrode was transferred to a 2mM Na2PtCl4 solution. The system reaction temperature was 30°C and the reaction time was 20min. A Pt single atomic layer based on a composite carrier was prepared, which was recorded as sample 5. Sample 5 was used as the cathode, and the proton exchange membrane (Nafion 211) and the anode (conventional electrode, Pt loading of 50μg / cm 2 ) assembled membrane electrode for battery performance evaluation. Since no perfluorosulfonic acid resin was added to the electrolyte solution and there was no proton conductor in the carrier, the proton conduction efficiency was low, which led to low electrode reaction efficiency and poor electrode performance. The test results of the electrode are as follows Figure 7 As shown in the figure, the open circuit voltage of a single cell is 0.93V, the cell voltage is only 0.50V at a current density of 1000, and the maximum power density is 500mW / cm 2 .

[0070] Comparative Example 2

[0071] Preparation and performance testing of Pt / C nanoparticles-supported catalytic electrode on the surface of ordered nanowire arrays

[0072] The composite carrier was prepared by cyclic voltammetry using carbon paper as the substrate. The concentration of pyrrole monomer in electrolyte solution 1 was 1.0M, the structure directing agent was 1.0M sodium hexadecylbenzenesulfonate solution, and the mass fraction of perfluorosulfonic acid resin was 1%. Under the three-electrode system, the cyclic voltammetry scan was performed in the range of -0.241V to 0.3V for 20 cycles, the reaction potential was 0.95V, the reaction time was 30min, and the electrolyte was kept in a constant temperature water bath at 35°C to obtain a composite nanowire ordered array carrier. An electrode with an ordered array carrier carrying Pt nanoparticle catalyst was prepared on the carrier surface by ultrasonic spraying, which was recorded as sample 6. The Pt loading of the electrode was controlled to 0.1mg / cm by controlling the slurry and spraying parameters. 2 Sample 6 was used as the cathode, with a proton exchange membrane (Nafion 211) and an anode (conventional electrode with a Pt loading of 50 μg / cm 2 ) assembled membrane electrode for battery performance and accelerated decay stability test. The test results of the electrode are as follows Figure 8 As shown, the open circuit voltage of the single cell is 0.96V, the battery voltage is 0.59V at a current density of 1000, and the maximum power density is 720mW / cm 2 After 10,000 cycles of accelerated scanning, the power density loss of the battery reached 18.9%, and its stability was far inferior to the ultra-low platinum loading ordered integrated electrode of the present invention (Example 2).

Claims

1. An ordered integrated electrode with ultra-low platinum loading, comprising a catalyst layer and a gas diffusion layer, characterized in that: The catalytic layer comprises a carrier, an active component and a metal substrate; the active component is Pt; the metal substrate is Pd or Pd-M, and the carrier is a composite ordered nanowire array; the active component Pt is coated on the surface of the composite ordered nanowire array carrier in the form of a thin film with a nanometer or sub-nanometer thickness; the metal substrate is located between the Pt thin film and the composite ordered nanowire array carrier in a layered form; M in the Pd-M is a noble metal; The thickness of the film is 0.1nm to 3nm; The loading amount of precious metal Pt on the electrode surface is 2-50 μg / cm 2 .

2. The electrode according to claim 1, characterized in that: The loading amount of Pd or Pd-M on the electrode surface is 50-100 μg / cm 2 .

3. The electrode according to claim 1, characterized in that: The composite ordered nanowire carrier is a composite of a conductive polymer and a proton conductor. The length of the composite ordered nanowire array is 2-15 μm and the diameter is 50-200 nm.

4. The method for preparing an electrode according to any one of claims 1 to 3, characterized in that: The specific preparation steps include: 1) Preparation of composite ordered nanowire array carriers In an electrolyte containing a proton conductor and a conductive polymer monomer, a composite nanowire ordered array carrier is prepared on a gas diffusion layer by using a cyclic voltammetry scanning method combined with a constant potential method or a cyclic voltammetry scanning method combined with a constant current method; the gas diffusion layer is carbon paper or carbon cloth; 2) Preparation of metal substrate layer: The composite ordered nanowire array carrier of step 1) is used as the processing object, and a metal substrate layer of Pd or Pd-M is prepared by a continuous ion layer adsorption reaction method; wherein M in the Pd-M is a noble metal; 3) Preparation of Pt thin film with ultra-low Pt loading In a three-electrode system, the metal substrate layer of step 2) is used as the working electrode and placed on a Cu 2+ In the electrolyte solution 2, the single atomic layer of Cu was deposited on the surface of the metal substrate layer using the underpotential deposition technique. Then, under the protection of an inert atmosphere, the working electrode was transferred to a Pt-containing 2+ In the precursor solution, a Pt single atomic layer based on a composite ordered carrier is prepared by substitution reaction, that is, an ordered integrated electrode is obtained; Alternatively, the underpotential deposition of Cu and the replacement reaction of Pt are repeated to prepare a continuous Pt thin film catalytic electrode with different atomic layer thicknesses.

5. The preparation method according to claim 4, characterized in that: The preparation method of the composite ordered nanowire array carrier in step 1) is specifically as follows: a. preparing an electrolyte solution 1, wherein the electrolyte solution 1 comprises a conductive polymer monomer, a proton conductor, a structure directing agent and a phosphate buffer; b. Using a carbon carrier as a reaction substrate, placing the electrolyte solution of step a in a constant temperature environment, and preparing a composite nanowire ordered array carrier of polypyrrole doped with perfluorosulfonic acid resin on the carbon carrier by self-catalytic growth using a cyclic voltammetry scanning method combined with a constant potential method, or a cyclic voltammetry scanning method combined with a constant current method; The proton conductor is a perfluorosulfonic acid resin, the conductive polymer is polypyrrole, and the monomer of the conductive polymer is a pyrrole monomer.

6. The preparation method according to claim 5, characterized in that: In step 1) a, the concentration of the pyrrole monomer is 0.5-1M; The structure directing agent is one of sodium hexadecyl sulfonate, sodium hexadecylbenzene sulfonate and a mixed solution of sodium p-toluene sulfonate; the concentration of the structure directing agent in the first electrolyte solution is 0.5-1M; The mass fraction of the perfluorosulfonic acid resin in the first electrolyte solution is 0.1%-10%; In step 1) b, the carbon carrier includes carbon paper, carbon cloth, or other carbon fibers other than carbon paper and carbon cloth; The specific steps of the cyclic voltammetry scanning method are as follows: firstly, the carbon support is activated by cyclic voltammetry scanning, the potential range of the activation treatment is -0.241V to 0.3V, the scanning number of circles is 10-30 circles, after the activation treatment, the setting of the constant potential method is: the reaction potential is set to 0.8V-0.95V, and the reaction time is 30min-2h; The constant temperature environment is a constant temperature water bath, and the temperature of the constant temperature water bath is 25-40°C.

7. The preparation method according to claim 4, characterized in that: The specific steps of preparing the metal substrate layer of Pd or Pd-M by continuous ion layer adsorption reaction method in step 2) are as follows: c. First, use deionized water to clean the surface of the composite ordered nanowire array carrier, and rinse repeatedly for 3-5 times; d. Soak the composite ordered nanowire array carrier obtained in step c in a mixed solution of SnCl2 and HCl solution to make Sn 2+ Adsorbed on the surface of the composite ordered nanowire array carrier, wherein the concentrations of SnCl2 and HCl solutions are 0.5-10 mM and 0.1-1 M, respectively, the immersion time is 30 min-2 h, and the temperature of the solution is maintained at 25-35 ° C; e. Transfer the carrier after the above immersion and immerse it in a precursor solution containing Pd, or a mixed precursor solution of Pd and a precious metal M. The immersion time is 30 minutes to 2 hours. The temperature of the solution is maintained at 25-35°C. After the reaction, a Pd or Pd-M metal base layer is obtained.

8. The preparation method according to claim 7, characterized in that: In step e, the Pd precursor solution is a mixed solution of 0.5-10mM PdCl2+0.1-1M HCl or 0.5-10mM (PdCl2+MCl x )+0.1-1M HCl mixed solution, wherein x is a number, and x is a value determined by the number of chlorine in M ​​metal chloride; MCl x M is a precious metal.

9. The preparation method according to claim 4, characterized in that: In step 3), the end potential of the underpotential deposition of Cu on the metal substrate layer is 0-0.1V; in step 3), the Cu 2+ The second electrolyte solution is a mixed solution of 0.01-0.2 mol / L H2SO4 and 0.01-0.2 mol / L CuSO4; The Pt-containing 2+ The precursor solution is 0.1-10mM K2PtCl4.

Citation Information

Patent Citations

  • Ordered catalyst layer and preparation and application thereof

    CN106410228A

  • Ordered gas diffusion electrode and preparation and application thereof

    CN103887531A

  • Fuel cell ultra-low platinum load self-humidifying membrane electrode and preparation method thereof

    CN109560310A